State‐of‐the‐Art Advances and Challenges of Iron‐Based Metal Organic Frameworks from Attractive Features, Synthesis to Multifunctional Applications. Issue 2 (7th December 2018) - Xia, Qi; Wang, Hou; Huang, Binbin; Yuan, Xingzhong; Zhang, Jingjing; Zhang, Jin; Jiang, Longbo; Xiong, Ting; Zeng, Guangming
Abstract: Metal organic frameworks (MOFs), as an original kind of organic–inorganic porous material, are constructed with metal centers and organic linkers via a coordination complexation reaction. Among uncountable MOF materials, iron‐containing metal organic frameworks (Fe‐MOFs) have excellent potential in practical applications owing to their many fascinating properties, such as diverse structure types, low toxicity, preferable stability, and tailored functionality. Here, recent research progresses of Fe‐MOFs in attractive features, synthesis, and multifunctional applications are described. Fe‐MOFs with porosity and tailored functionality are discussed according to the design of building blocks. Four types of synthetic methods including solvothermal, hydrothermal, microwave, and dry gel conversion synthesis are illustrated. Finally, the applications of Fe‐MOFs in Li‐ion batteries, sensors, gas storage, separation in gas and liquid phases, and catalysis are elucidated, focusing on the mechanism. The aim is to provide prospects for extending Fe‐MOFs in more practical applications. Abstract : Iron‐containing metal organic frameworks (Fe‐MOFs) have attracted intensive attention due to their unique topological structure and exploitable properties. Owing to the functional applications in electrochemical devices and its adsorbent and photo‐electrocatalyst properties, Fe‐MOFs have become an emerging hot topic for high‐performance energy conversion devices, gas/liquid separation, and advanced catalysis.